The legacy of attending a sustainably friendly school: Ysgol San Sior, a place of possibilities for a sustainable world - Diane Boyd; Naomi McLeod; Ian Jones (Educational Futures)
This research explores the value of attending a sustainable friendly school in Llandudno in North Wales (Ysgol San Sior) for children aged 3 – 11 to ascertain the impact of sustainability in everyday life, as currently there is no empirical research that involves young children in relation to this focus. Our research builds on previous research and literature that reinforces how underpinning personal values, attitudes and dispositions are formed in the early years (Boyd, 2018; Siraj-Blatchford et al, 2010), In doing so, it demonstrates the valued foundations and contribution of early childhood education and the importance of positive dispositions to learning nurtured through first-hand experiences and engagement that can inform later values and decisions in everyday life (McLeod and Anderson, 2019). This aligns conceptually with UNESCO’s key competencies for Education for Sustainability (2017) which include collaboration, critical thinking, self-awareness, systems thinking and integrated problem-solving starting in the early years. Each resonates with the philosophy of Reggio Emilia which incorporates empowerment, agency, critical thinking and transformation for greater equity and social justice. Collectively, these elements, informed our use of co-constructed research methods. An ethical approach was embedded so all participants were consulted and respected at every stage, for example, including the name of the school in the research. Our research started by valuing the experiences and views of the very youngest children in the school who were aged three years old, which is the foundation the school is built upon, rather than viewing them as being too young to participate. The most appropriate design for listening to participants’ views, especially young children, was a participatory, rights based approach which is concerned with both the process and the end product of inquiry and was about working ‘with’ rather than doing to in order to explore concepts that were personally important to the participants. In doing so, we used semistructured conversations. In contrast to the outcome-driven model of education often dominant today, our interpretive thematic analysis reveals how attending Ysgol San Sior nurtures positive dispositions to learning associated with caring, compassion, empathy and agency, and deep intra-personal qualities that make possible an appreciation of ‘otherness’ such as caring for the non-human world and empathy for the disadvantaged and vulnerable. These empathetic attitudes empower children (and adults) to make interconnected decisions (including business awareness of economic sustainability and enterprise), and act for a more sustainable world. Valuing the voices of all was made possible through the co-constructed leadership of Ian Jones the Headteacher, whose passion informs an inter-related understanding of sustainability and a willingness to question the purpose of education within the context of climate change. Our research also indicates how the seamless Welsh curriculum builds on the foundational base of early childhood, through primary and beyond, to inform all areas of lifelong learning and nurtures a strong sense of self and being Welsh. In doing so we recognise the need to slow down and to refocus and nurture relationships that develop empathy, compassion and kindness for others.